2018
DOI: 10.1097/md.0000000000009612
|View full text |Cite
|
Sign up to set email alerts
|

Functional performance comparison between real and virtual tasks in older adults

Abstract: Introduction:Ageing is usually accompanied by deterioration of physical abilities, such as muscular strength, sensory sensitivity, and functional capacity, making chronic diseases, and the well-being of older adults new challenges to global public health.Objective:The purpose of this study was to evaluate whether a task practiced in a virtual environment could promote better performance and enable transfer to the same task in a real environment.Method:The study evaluated 65 older adults of both genders, aged 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
19

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 46 publications
(54 reference statements)
0
35
0
19
Order By: Relevance
“…As relatively new technological tools, exergames are increasingly being used as an alternative to conventional rehabilitation-based exercises to improve daily PA levels and increase physical fitness in older adults [52]. Research showed that older adults exposed to exergame training are able to improve a variety of physical functions, such as balance control, cardiorespiratory fitness, and gait speed, among others [53,54]. Exergame programs also provide light-intensity exercises and elicit significantly greater energy expenditure when compared with a resting state [55].…”
Section: Discussionmentioning
confidence: 99%
“…As relatively new technological tools, exergames are increasingly being used as an alternative to conventional rehabilitation-based exercises to improve daily PA levels and increase physical fitness in older adults [52]. Research showed that older adults exposed to exergame training are able to improve a variety of physical functions, such as balance control, cardiorespiratory fitness, and gait speed, among others [53,54]. Exergame programs also provide light-intensity exercises and elicit significantly greater energy expenditure when compared with a resting state [55].…”
Section: Discussionmentioning
confidence: 99%
“…The participant must rest his/her hand next to the keyboard of the computer and then press the space key at exactly the moment when the last (target) sphere lights up. The software provides immediate feedback on the success or otherwise of the task by means of different previously demonstrated sounds and colours [for more details, see ( 8 , 17 , 67 , 68 )]. If the participant anticipates or delays the timing of the stimulus, a red light will appear around the feedback; if he/she hits the target, a green light will appear ( Figure 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…The magnitude and direction of error of each participant in anticipating or delaying the arrival of the light is recorded by the software in milliseconds. The object is to evaluate the time difference between the participant's response and the arrival of the object at the target location (accuracy) and his/her global temporal precision and therefore his/her coincidence–anticipation ability ( 8 , 17 , 67 , 69 , 70 ).…”
Section: Methodsmentioning
confidence: 99%
“…One of these opportunities could be the appropriate use of technology. Examples of new technology are games with virtual reality for rehabilitation 31 , recovery of children with Duchenne muscular dystrophy 32 , inclusion of older people 33 , or improving literacy of individuals with intellectual disabilities 34 . The advancement of the "Internet of Things" (IoT) technology has a potential to be used in medical and health care, with a development of applications that will change the way of living 35 , especially in remote areas in Brazil.…”
mentioning
confidence: 99%